Komposisi Hasil Tangkapan Bubu Berlampu Dan Bubu Berumpan Di Sekitar Keramba Jaring Apung - Machmud A. I. Leisubun; Jacobus W. Mosse (Universitas Pattimura, 2025)
Fish traps (bubu) are passive fishing gears that can be operated across a variety of habitats. However, the deployment of bubu around floating net cages (FNCs) has received limited scientific attention. This study aimed to examine the species composition and productivity of bubu traps using different bait characteristics. Two types of traps—those baited with Decapterus sp. (momar) and those equipped with lights—were operated around FNCs during morning and afternoon periods. Four light colors—red, yellow, blue, and white—were tested, each yielding distinct results. A total of 150 individuals were captured, comprising 26 fish species and several benthic organisms such as crabs, sea cucumbers, and sea urchins. The highest productivity was recorded in baited traps, averaging 5.8 catches per trip, predominantly composed of crabs. Traps with blue light produced an average of 5.0 fish per trip, exclusively capturing fish species. White, yellow and red light traps, in contrast, were dominated by sea urchins alongside fish catches. Based on economic value, the catches from baited traps consisted of commercially important carnivorous species such as groupers (5.2%), scads (5.2%), and emperors (10.3%). In comparison, light-baited traps tended to attract planktivorous fish. The use of bubu with various bait characteristics may serve not only for fishing purposes but also as a tool for ecological observation as anthropogenic impact, such as areas surrounding FNCs.